UAV path planning method for avoiding restricted areas - Choi, Kwanghoon; Kim, Jai Hoon (Intelligent Service Robotics, 2021)
Recently, the industry of drone systems has come into the spotlight because a new potential market has been revealed. A considerable number of drones are deployed worldwide as they can be used in many applications, providing a broad range of services, such as monitoring the surrounding environment, delivering services, in farming, and in rescue activities from disasters to accidents. This expansion is fostering the development of a comprehensive approach, including the construction of general systems, such as cyber-physical systems and IoT middleware platforms. In terms of the quantitative aspects of the drone industry, we still have many issues to solve and improve, such as privacy protection, human safety, improvement in resources, and specifically, power consumption and efficiency. To overcome these problems, systems must be able to generate an efficient and easy-to-follow path that is able to dynamically adjust to new situations. Thus, we propose an ONLINE/OFFLINE path planning algorithm and evaluate the results of a simulation using a drone kit with a software-in-the-loop simulator. The ONLINE and OFFLINE path planning algorithm is applied to discover a path to the destination in a changeable situation, and it is simulated on a real-life map, which includes a restricted area.
Keywords: Drone; Drone system; Path finding; Path planning method; Path-planning algorithm; Potential markets; Rescue activities; Sensors network; Spatiotemporal; Surrounding environment; Cyber-physical systems; Drone; Path finding; Path planning; Sensor network; Spatiotemporal; UAV